Simvastatin and fluvastatin attenuate trauma-induced cell death and catabolism in human cartilage - Riegger, Jana; Maurer, Svenja; Pulasani, Sai; Brenner, Rolf E. (Frontiers in Bioengineering and Biotechnology, 2022)
Joint injuries are known to induce pathomechanisms that might lead to posttraumatic osteoarthritis (PTOA). In this regard, statins with their pleiotropic effects could represent potential therapeutic agents in preventing the development of PTOA. Therefore, we investigated the effects of simvastatin and fluvastatin in a drop-tower-based human ex vivo cartilage trauma model. After 7 d, a mechanical impact (0.59 J) resulted in a decrease of the cell viability and increased expression of catabolic enzymes in cartilage explants. Simvastatin and fluvastatin treatment of impacted cartilage demonstrated cell protective effects in a concentration dependent manner. Moreover, statin therapy exhibited chondroprotective effects as demonstrated by attenuated expression of MMP-2 and MMP-13 as well as subsequent breakdown of collagen type II (after impact). Further analysis indicated antioxidative properties of the statins by upregulating the gene expression of SOD2 and suppression that of NOX2 and NOX4. Despite its protective effects, simvastatin impaired the biosynthesis of collagen type II, which was confirmed during chondrogenic redifferentiation of high passage chondrocytes. However, while long-term administration of statins for 4 weeks impaired chondrogenic redifferentiation, addition of Simvastatin at low concentrations for one week exhibited a slightly promoting effect. In conclusion, our data imply that simvastatin and fluvastatin are suitable in terms of initial harm reduction after cartilage trauma.